Time to Local Recurrence as a Predictor of Survival in Patients With Soft Tissue Sarcoma of the Extremity and Abdominothoracic Wall - Liang, Yao; Guo, Tianhui; Hong, Dongchun; Xiao, Wei; Zhou, Zhiwei; Zhang, Xing (Frontiers in Oncology, 2020)
Objective: The purpose of this retrospective study was to identify the prognostic significance of time to local recurrence (TLR) with regard to overall survival (OS) and survival after local recurrence (SAR) in patients with soft tissue sarcoma (STS) of the extremity and abdominothoracic wall. Methods: We identified 477 patients who underwent R0 resection for localized STS of the extremity and abdominothoracic wall, from January 1995 to December 2016, of whom 190 patients developed local recurrence as their first recurrent event. Based on TLR, patients were divided into two groups: early local recurrence (ELR, <12 months) and late local recurrence (LLR, ≥12 months). The Kaplan–Meier method and Cox regression analysis were used to estimate the OS and SAR, and to identify factors associated with patient outcomes. Results: The median follow-up time for the entire cohort was 118.4 months, and was 118.5 months for the 190 patients who developed local recurrence. Deep tumor location (HR 1.73, 95% CI 1.27-2.37, P = 0.001) and tumor grade ≥2 (G2 vs. G1: HR 1.75, 95% CI 1.21-2.53, G3 vs. G1: HR 2.57, 95% CI 1.66-3.98, P < 0.001) were associated with a higher rate of local recurrence. There were 99 patients in the ELR group and 91 in the LLR group, with a median TLR of 10.8 months for the entire cohort. Patients from the ELR group had a shorter OS and a lower 5-year OS rate than the LLR group. Univariate and multivariate analyses demonstrated TLR as an independent prognostic factor for SAR and OS, in addition to tumor grade. Also, surgical treatment and absence of metastasis after local recurrence were associated with longer SAR. Conclusions: In patients with STS of the extremity and abdominothoracic wall, ELR after R0 resection indicated a worse prognosis than those with LLR, and TLR can be considered an independent prognostic factor for OS and SAR. Furthermore, local recurrence was significantly influenced by the depth and the histopathological grading of the primary tumor, and reoperation after local recurrence could improve survival, which means salvage surgery may still be the preferred treatment when there are surgical indications after recurrence.